HUBUNGAN SENAM NIFAS DENGAN PROSES INVOLUSI PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS TAWANGSARI KABUPATEN MOJOKERTO - Wiwit Sulistyawati; Nurun Ayati Khasanah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
The purpose of this research to know the relationship between puerperal gymnastics with the process of uterine involution in ​​Puskesmas Tawangsari Mojokerto. This type of research used survey method. The independent variables in the research that is puerperal gymnastics and dependent variable is the process of uterine involution. This study was conducted on January 2nd to May 28th, 2017. Population was all postpartum in the work area of ​​Puskesmas Tawangsari where sampling using consecutive sampling technique obtained 17respondents. Datacollected through questionnaires then performed data management, then presented in the form of distribution tables frequency. The result of this research showed that more than 50% of respondents who often do puerperal gymnastics experienced a fast uterine involution as much as 9 (52,9%) respondents, while the rest often do puerperal gymnastics but experiencing slow uterine involution. Based on Fisher Exact Probability test at α (0,05) got P value (0,02) because P < (0,05) then H0 rejected mean there is relation between puerperal gymnastic and uteri involution at post partum mother in working area of ​​puskesmas Tawangsari Regency of Mojokerto. Postpartum women who are reluctant to do postpartum exercises are influenced by several factors, among others, do not know how to or exercising childbirth, the lack of support from the family, and reluctant or lazy to do puerperal gymnastics. Therefore health workers are expected to provide counseling about postpartum and held puerperal gymnastic classes at puskesmas or BPM.